Early tourism writing at the Jagiellonian University, Kraków (15th C.-mid-17th C.) - Jackowski, Antoni (Turyzm/Tourism, 2009)
The author attempts to outline early tourism writing by professors and graduates from the Kraków Academy (Akademia Krakowska), the majority of which are geographic and cartographic works. Among the authors, Jan Długosz, Wawrzyniec Korwin, Jan z Głogowa, Maciej z Miechowa (Miechowita), Bernard Wapowski and Marcin Kromer should be mentioned.